2021
DOI: 10.1155/2021/1601565
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Roles of Trogocytosis in Immunity, the Nervous System, and Development

Abstract: Trogocytosis is a general biological process that involves one cell physically taking small parts of the membrane and other components from another cell. In trogocytosis, one cell seems to take little “bites” from another cell resulting in multiple outcomes from these cell-cell interactions. Trogocytosis was first described in protozoan parasites, which by taking pieces of host cells, kill them and cause tissue damage. Now, it is known that this process is also performed by cells of the immune system with impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 103 publications
(217 reference statements)
0
22
0
Order By: Relevance
“…During TCR/MHC interaction between T cells and APCs, the IS directs the actin network close to the clusters of TCR complexes ( Dopfer et al., 2011 ) via the PI3K and two small GTPases RhoG and RRas ( Uribe-Querol and Rosales, 2021 ). As Rho compounds are well recognized for their key role in F-actin contraction and polymerization ( Lou et al., 2019 ), it is likely that Rho molecules are recruited near the clustering TCR molecules and then bind actin filaments, triggering synchronized contraction that results in an engulfment-like rearrangement of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…During TCR/MHC interaction between T cells and APCs, the IS directs the actin network close to the clusters of TCR complexes ( Dopfer et al., 2011 ) via the PI3K and two small GTPases RhoG and RRas ( Uribe-Querol and Rosales, 2021 ). As Rho compounds are well recognized for their key role in F-actin contraction and polymerization ( Lou et al., 2019 ), it is likely that Rho molecules are recruited near the clustering TCR molecules and then bind actin filaments, triggering synchronized contraction that results in an engulfment-like rearrangement of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Why are certain plasma membrane molecules trogocytosed and not others? This is unknown, and it is probably related to the unknowledge of the mechanism(s) of trogocytosis [ 5 , 31 ]. Of note, the co-trogocytosis of CD4 with CCR5 or CXCR4 could have resulted in the HIV-1 infectibility of NK cells in the same way as trans-synaptic acquisition of CD21 by NK cells allowed EBV binding [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil trogocytosis were seen in different modes including cancer cell killing with coated antibody, parasite removal, excess sperm removal, and cellular communication with other immune cells (Uribe-Querol and Rosales 2021 ). While several studies have shown trogocytosis between neutrophils and immune cells, very little is known about neutrophil trogocytosis with non-immune cells such as endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…A newly-reported function of neutrophils is trogocytosis or membrane transfer with neighboring cells, to modulate innate and adaptive immune responses (Kruger et al 2015 ; Tsai 2021 ). Trogocytosis has been observed in many organisms including protozoa, nematode, and many different cell types in higher organisms (Uribe-Querol and Rosales 2021 ). There are different modes of trogocytosis observed including cell killing or cell-to-cell communication (Miyake and Karasuyama 2021 ).…”
Section: Introductionmentioning
confidence: 99%